Physiological and proteomics analyses of Holm oak (Quercus ilex subsp. ballota [Desf.] Samp.) responses to Phytophthora cinnamomi - Sghaier-Hammami, Besma; Valero-Galvàn, José; Romero-rodríguez, Mª Cristina; Navarro-Cerrillo, Rafael Mª Ma; Abdelly, Chedly; Jorrín-novo, Jesús (Plant Physiology and Biochemistry, 2013)
Phytophthora cinnamomi is one of the agents that trigger the decline syndrome in Quercus spp., this being a serious threat to Mediterranean Holm oak forest sustainability and reforestation programs. Quercus ilex responses to Phytophthora cinnamomi have been studied in one-year olds seedlings from two Andalucía provenances, assessing the physiological water status and photosynthesis-related parameters. Upon inoculation with mycelium a reduction in water content, chlorophyll fluorescence, stomatal conductance and gas exchange was observed along a 90 days post inoculation period in both provenances. The reduction was higher in the most susceptible (SSA) provenance, than in the most tolerant (PCO), being these typical plant responses to drought stress. Leaf protein profiles were analyzed in non-inoculated and inoculated seedlings from the two provenances by using a 2-DE coupled to MS proteomics strategy. Ninety seven proteins changing in abundance in response to the inoculation were successfully identified after MALDI–TOF–TOF analyses. The largest group of variable identified proteins were chloroplasts ones, and they were involved in the photosynthesis, Calvin cycle and carbohydrate metabolism. It was noted that a general tendency was a decrease in the protein abundance as a consequence of the inoculation, being it less accused in the least susceptible, the Northern provenance (PCO), than in the most susceptible, the Southern provenance (SSA). This trend is clearly manifested in photosynthesis, amino acid metabolism and stress/defence proteins. On the contrary, some proteins related to starch biosynthesis, glycolysis and stress related peroxiredoxin showed an increase upon inoculation. These changes in protein abundance were correlated to the estimated physiological parameters and have been frequently observed in plants subjected to drought stress.
From Duplicate 1 (Physiological and proteomics analyses of Holm oak (Quercus ilex subsp. ballota [Desf.] Samp.) responses to Phytophthora cinnamomi - Sghaier-Hammami, Besma; Valero-Galvàn, José; Romero-rodríguez, Mª Cristina; Navarro-Cerrillo, Rafael Mª; Abdelly, Chedly; Jorrín-novo, Jesús)From Duplicate 1 (Physiological and proteomics analyses of Holm oak (Quercus ilex subsp. ballota [Desf.] Samp.) responses to Phytophthora cinnamomi - Sghaier-Hammami, Besma; Valero-Galvàn, José; Romero-rodríguez, Mª Cristina; Navarro-Cerrillo, Rafael Mª; Abdelly, Chedly; Jorrín-novo, Jesús)The following values have no corresponding Zotero field: publisher: Elsevier Masson SAS accession-num: 23962806
Keywords: Gene Expression Regulation; Holm oak decline; Holm oak proteomics; Phytophthora; phytophthora cinnamomi; Phytophthora: physiology; Plant; Plant Proteins; Plant Proteins: genetics; Plant Proteins: metabolism; Plant: genetics; Plant: physiology; Proteomics; Proteomics: methods; Quercus; Quercus ilex; Quercus: microbiology

Spatial patterns of soil pathogens in declining Mediterranean forests: implications for tree species regeneration. - Gómez-Aparicio, LORENA; Ibáñez, Beatriz; Serrano, María S.; De Vita, Paolo; Avila, José M.; Pérez-Ramos, Ignacio M.; García, Luis V.; Esperanza Sánchez, M.; Marañón, Teodoro (The New phytologist, 2012)
Soil-borne pathogens are a key component of the belowground community because of the significance of their ecological and socio-economic impacts. However, very little is known about the complexity of their distribution patterns in natural systems. Here, we explored the patterns, causes and ecological consequences of spatial variability in pathogen abundance in Mediterranean forests affected by oak decline. We used spatially explicit neighborhood models to predict the abundance of soil-borne pathogen species (Phytophthora cinnamomi, Pythium spiculum and Pythium spp.) as a function of local abiotic conditions (soil texture) and the characteristics of the tree and shrub neighborhoods (species composition, size and health status). The implications of pathogen abundance for tree seedling performance were explored by conducting a sowing experiment in the same locations in which pathogen abundance was quantified. Pathogen abundance in the forest soil was not randomly distributed, but exhibited spatially predictable patterns influenced by both abiotic and, particularly, biotic factors (tree and shrub species). Pathogen abundance reduced seedling emergence and survival, but not in all sites or tree species. Our findings suggest that heterogeneous spatial patterns of pathogen abundance at fine spatial scale can be important for the dynamics and restoration of declining Mediterranean forests.
The following values have no corresponding Zotero field: accession-num: 22428751
Keywords: Biological; Forest decline; Host-Pathogen Interactions; Mediterranean Region; Models; neighborhood models; Phytophthora; Phytophthora: physiology; Pythium; Pythium: physiology; Quercus; Quercus suber; Quercus: microbiology; regeneration dynamics; Seedling; Seedling: microbiology; Soil Microbiology; soil texture; soil-borne pathogens; species coexistence

Genetic diversity of European populations of the oak fine-root pathogen Phytophthora quercina - Cooke, D. E. L.; Jung, T.; Williams, N. a; Schubert, R.; Osswald, W.; Duncan, J. M. (Forest Pathology, 2005)
The recently discovered oak-specific fine root plant pathogen Phytophthora quercina is a significant factor in the current phase of European oak decline but its origins and ecology are poorly understood. A genome-wide analysis of 260 amplified fragment length polymorphism (AFLP) markers was used to examine the genetic diversity of 72 isolates from five oak species at 28 sites in Germany (particularly Bavaria), Italy, France, Hungary and the UK. Within-site diversity was examined at 16 sites. The limited genetic diversity (within and between sites) and lack of genetic substructuring according to geographic origin or host species suggest the rapid spread of a relatively recently introduced species. Two subgroups were distinguished and these may reflect an initial introduction of isolates of two different genetic backgrounds. The relatively low genetic diversity is probably because of the predominantly inbreeding (homothallic) nature of P. quercina. However, evidence of limited intra-site diversity, temporal variation and the lack of clonality within the European population suggest that some diversity is being maintained by occasional outcrossing and turnover of a reservoir of long-lived soil-borne oospore (sexually derived) inoculum
Keywords: AFLP; decline; diversity; pathogen (voyant); Phytophthora

Etiología de las podredumbres radicales de plántulas de QUERCUS SPP. Y PINUS HALEPENSIS EN VIVEROS FORESTALES DE ANDALUCÍA - Andicoberry, S.; LORA, F.; SÁNCHEZ, E.; Trapero, A. (III Congreso Forestal Español, 2001)
A disease surey carried out during 1998-99 showed that holm oak (Quercus ilex) and Aleppo pine (Pinus halepensis) seedlings were affected by damping-off and root rot in three forest nurseries in Andalucía, southern Spain. A similar problem was detected affecting four species of Quercus (Q. coccinea, Q. faginea, Q. ilex, and Q. suber) in a forest nursery in 2000. Three species of Phytophthora (P. cinnamomi, P. cryptogea, and P. drechsleri) were isolated from holm oak feeder roots, and P. drechsleri was isolated from feeder roots of Aleppo pine in the first survey in 1998-99. In the second survey, Cylindrocarpon didymum was isolated from the feeder roots of the four Quercus spp. essayed, and C. destructans was isolated only from Q. faginea. Pathogenicity tests were conducted using 1 year-old healthy plants of cork oak, holm oak and Aleppo pine. Isolates of the three Phytophthora species were pathogenic to the three host species, inducing root rot and plant death. Holm oak was the most susceptible host and P. cinnamomi was the most virulent species. Isolates of Cylindrocarpon were pathogenic to cork oak and holm oak causing root rot, yellowing, defoliation, and plant death.
The following values have no corresponding Zotero field: periodical: III Congreso Forestal Español pub-location: Granada
Keywords: Cylindrocarpon; Phytophthora; Quercus coccinea; Quercus faginea; Quercus ilex; Quercus suber